A atuação do Serviço de Proteção aos Índios no Rio Grande do Sul: uma análise a partir do Relatório Figueiredo (1963-1968) - Flores, Andressa de Rodrigues (Universidade do Vale do Rio dos Sinos, 2019)
This dissertation has as its goal to reflect about the omissions and violations of indigenous rights perpetrated by the Brazilian State, privileging the study of the denunciations of violence committed by agents of the extinct Indian Protection Service (SPI) against the indigenous populations of Rio Grande do Sul, based on the Relatório Figueiredo. This research is justified by the need to carefully examine still little known facts, which occurred in the beginning of the Civil-Military Dictatorship period of Brazil, particularly when it comes to the indigenous populations. The temporal frame of this analysis spans from 1963 to 1968, a period in which the denunciations against the SPI became public at a national and international level. The geographical frame comprises the four Indigenous Sites of Rio Grande do Sul, which were administered by the SPI, being Cacique Doble (Lagoa Vermelha), Guarita (Tenente Portela), Nonoai (Municipality of Nonoai) and Paulino de Almeida (Getúlio Vargas). The problematic of this research consists of, based on the historical context in which this violence occurred, identifying who were the participants and what was their connection with SPI, as well as describing and discussing the types of violence that were committed in these indigenous posts. For this purpose, we resort to the reference studies of the New Indigenous History and those that address indigenous issues in Rio Grande do Sul, indigenous politics in Brazil, the history of the Kaingang and the situation of violence against indigenous populations based on the Relatório Figueiredo. The sources utilized include the documentation of the Relatório Figueiredo, articles published by the press and the Boletins Internos produced by SPI. In this research we aim to, through documentary sources, analyze the irregularities and violence committed by the SPI against the indigenous populations residing in the PI in Rio Grande do Sul, registered in the Relatório Figueiredo, as well as describe the context of these irregularities, examining the relationship that SPI chiefs/inspectors maintained with indigenous people and PI officials. We also focus on identifying and discussing the practices of violence committed by SPI officials, based on the definition of a typology of the crimes, which guided the analysis.
Keywords: Relatório Figueiredo; SPI; Postos Indígenas; Violência; Denúncias; Rio Grande do Sul; Relatório Figueiredo; SPI; Indigenous Posts; Violence; Denunciations; Rio Grande do Sul; ACCNPQ::Ciências Sociais Aplicadas::Comunicação